Rethinking Delegated Legislation in Indonesian Legal System - Al-Fatih, Sholahuddin; Safaat, Muchamad Ali; Widiarto, Aan Eko; Uyun, Dhia Al; Rahmat, Al Fauzi (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: Delegated legislation in Indonesia is a new type of legislation that should be interpreted and ruled carefully. However, nowadays, the Indonesian legal system has no fixed term for delegated legislation and no hierarchy on it. Furthermore, as many as 57.677regulations at the level of Ministries, Agencies and State Institutions have the potential to overlap regulations and become subject to judicial review in the Supreme CourtPurpose/Objective Study: This article aims to analyze the best term and hierarchy of delegated legislation in the legal system in Indonesia.Design/Methodology/Approach: This legal research conducted normative studies, by examining previous studies on delegated legislation and Electronic and Information Transaction (EIT) law to imagine the delegated legislation type and hierarchy. The data was analyzed by a prescriptive method to give a new idea regarding delegated legislation in Indonesia's legal system.Findings: This paper finds no fixed term for delegated legislation in the Indonesian legal system. There is a loophole in the Indonesian legal system related to delegated legislation. However, some scholars argue that delegated legislation in Indonesia can be found in Government Regulation, Presidential Regulation, Local Regulation and beleidsregel in Article 8 Paragraph (1) Law Number 12 of 2011 concerning Establishing Statutory Regulation and its amendment. As a suggestion, the amendment of the Law on Establishing Statutory Regulation is a must in carrying delegated legislation definition, purpose and hierarchy.Paper Type: Research Article